2008
DOI: 10.1021/om800040f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structure, and Reactivity of Discrete Branched Oligogermanes

Abstract: The hydrogermolysis reaction of PhGeH3 serves in the synthesis of discrete branched oligogermanes. Treatment of PhGeH3 with 3 equiv of the α-germyl nitriles R3GeCH2CN (R3 = Ph3 or Bu2CH2CH2OEt), which are generated in situ from the corresponding amides R3GeNMe2 and CH3CN, furnishes the tetragermanes PhGe(GePh3)3 and PhGe(GeBu2CH2CH2OEt)3 in excellent yield. The crystal structure of PhGe(GePh3)3 was determined. This compound is the first branched oligogermane to be structurally characterized. Reaction of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(84 citation statements)
references
References 43 publications
6
76
2
Order By: Relevance
“…Compound 3 exhibits a l max at 212 nm (ε ¼ 3.3 Â 10 4 L mol À1 cm À1 ) [3] that is considerably blue-shifted relative to those for 1 and 2 that were observed at 251 [4,5] and 256 nm [2] (respectively). A similar trend was observed among the related branched oligosilanes (Ph 3 Si) 3 SiH, (PhMe 2 Si) 3 SiPh and (Me 3 Si) 4 Si, where (Ph 3 Si) 3-SiH and (PhMe 2 Si) 3 SiPh exhibit a l max values at 240 and 243 nm (respectively) in their UV/visible spectra, both of which are significantly red-shifted relative to that for (Me 3 Si) 4 Si observed at 210 nm [12].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Compound 3 exhibits a l max at 212 nm (ε ¼ 3.3 Â 10 4 L mol À1 cm À1 ) [3] that is considerably blue-shifted relative to those for 1 and 2 that were observed at 251 [4,5] and 256 nm [2] (respectively). A similar trend was observed among the related branched oligosilanes (Ph 3 Si) 3 SiH, (PhMe 2 Si) 3 SiPh and (Me 3 Si) 4 Si, where (Ph 3 Si) 3-SiH and (PhMe 2 Si) 3 SiPh exhibit a l max values at 240 and 243 nm (respectively) in their UV/visible spectra, both of which are significantly red-shifted relative to that for (Me 3 Si) 4 Si observed at 210 nm [12].…”
Section: Resultsmentioning
confidence: 88%
“…The preparation of (Ph 3 Ge) 3 GeH (1) and (Ph 3 Ge) 3 GeMe was first reported in 1963 [6], and the compounds (PhCl 2 Ge) 3 GePh [7] and (PhX 2 Ge) 3 GePh (X ¼ Me, MeO, MeS, Me 2 N, Et 2 P) [8] were reported in the early 1970s. In light of the successful use of the hydrogermolysis reaction for the stepwise synthesis of linear oligogermanes, we have used this method for the synthesis of the branched oligogermanes (Ph 3 Ge) 3 GeH (1) [4,5] and (Ph 3 Ge) 3 GePh (2) [2]. The former compound was converted into the halide-substituted branched oligogermanes (Ph 3 Ge) 3 GeX (X ¼ Cl, Br, I) but neither the hydride 1 nor the amide (Ph 3 Ge) 3 GeNMe 2 that was obtained from (Ph 3 Ge) 3 GeCl could be employed for the synthesis of the neo-pentane analogue (Ph 3 Ge) 4 Ge via the hydrogermolysis reaction due to the steric effects of the four triphenylgermyl-groups [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of Ph 3 GeGeMe 3 (4) with one equivalent of trifluoromethanesulfonic acid. Synthesis of Ph 2 (OTf)GeGeMe 3 (9) Trifluoromethanesulfonic acid (0.11 ml, 1.19 mmol) was added at 0 S to the solution of Ph 3 GeGeMe 3 (4) (0.50 g, 1.19 mmol) in CH 2 Cl 2 (10 ml). The reaction mixture was heated to room temperature and for 2 h. The volatiles were removed under vacuum, hexane and CH 2 Cl 2 were added to residue up to dissolving and solution was stored at À30 S. The crystals formed were isolated and dried under reduced pressure.…”
Section: Synthesis Of Ph 2 Ge(otf)ge(otf)ph 2 (7)mentioning
confidence: 99%
“…Yield 0.23 g (39%). 1 Under prolonged storage of the concentrated solution of Ph 2 (OTf)GeGeMe 3 (9) in CH 2 Cl 2 the crystals of Ph 2 (OTf)GeGePh 2-GeMe 3 (9a) suitable for X-ray analysis were obtained.…”
Section: Synthesis Of Ph 2 Ge(otf)ge(otf)ph 2 (7)mentioning
confidence: 99%
“…Our synthetic methodology can be employed for the systematic variation of not only the number of germanium atoms in the GeeGe backbone but also of the organic substituents attached to the germanium atoms in the chain. This was not possible using other previously reported synthetic methods, and we have prepared both linear [41,42,44,45] and branched [43] oligogermane systems using this method. It has been demonstrated that both the number of catenated germanium atoms and the electronic attributes of the attached organic substituents affect the relative energies of the frontier orbitals in these systems.…”
Section: Introductionmentioning
confidence: 99%